A Schulman posts higher sales and income in 1Q fiscal 2015. Issue 3 (March 2015) - Unknown
Abstract : Masterbatch and compounds producer A. Schulman, Inc posted net income from continuing operations of US13.2 million for its fiscal first quarter ended 30 November 2014, a 6.5% increase compared with 12.4 million a year earlier. The company achieved net sales of 615.1 million for the 2015 quarter, up 5% from 585.4 million the previous year. Excluding the negative effect of foreign currency translation, revenues would have increased by 9.5% year on year to 641.3 million, the company reports.